Comparative Analysis of Good Corporate Governance Implementation Based on ASEAN Corporate Governance Scorecard from the Indonesian Banking Industry - Ramli, Ramsey; Setiany, Erna (Jurnal Keuangan dan Perbankan, 2021)
The phenomenon of Good Corporate Governance (GCG) implementation in Indonesia is still lagging compared to the other countries in the ASEAN region. For the first time, Indonesia only placed 2 (two) issuers from the banking industry as the ASEAN Top 50 publicly listed companies in the event of Awards and Recognition of Top ASEAN Publicly Listed Companies in 2015. This study aims to analyze significant difference of the GGG implementation among the Top 50 and non-Top 50 ranked banks using ASEAN Corporate Governance Scorecard (ACGS) index and its correlation with the human resources (HR) policies. The data analysis of this study uses descriptive and nonparametric comparative analyses with the Mann-Whitney test method. Despite some limitations, the empiric results showed that there are significant differences in the implementation of the GCG among the Top 50 and non-Top 50 ranked banks as proxied by the total score of the ACGS. On the contrary, there are no significant differences in the HR policies as proxied by the ACGS score on the Role of Stakeholders.DOI: https://doi.org/10.26905/jkdp.v25i1.4779